Accessing Indigenous Long-Term Care - Gionnas, Danielle; Bianchi, Andria; Benoit, Leonard; Rodrigues, Kevin (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2021)
The purpose of this commentary is to present and respond to the gap that currently exists in providing culturally inclusive residential long-term care options for Indigenous peoples in Ontario. After presenting statistics regarding the Indigenous population and long-term care options, we argue that we have an ethical responsibility to offer more culturally inclusive long-term care.